IDENTITAS DAN KONFLIK MORAL DALAM GALATEA KARYA EMILY SHORT DAN DE BARON KARYA VICTOR GIJSBERS: STUDI FIKSI INTERAKTIF DALAM ANALISIS WACANA - Seswita, Seswita; Az-Zahrai , Asyifa Ratu (Linguistika Kultura, 2025)
This study analyzes two works of interactive fiction, Galatea (2000) by Emily Short and De Baron (2006) by Victor Gijsbers, to examine how identity and moral conflicts are constructed within interactive narratives. This study employs discourse analysis, particularly focusing on Stuart Hall’s concept of identity, as well as the principles of positioning and representation in social discourse. A qualitative method with close reading techniques is applied to both texts to explore how characters construct and negotiate their identities in relation to other characters and social expectations. The results indicate that Galatea emphasizes identity issues through a non-linear narrative structure, while De Baron highlights moral conflicts shaped by character positioning and social representation within a linear narrative. These findings suggest that interactive fiction can engage with complex issues of identity and morality in ways comparable to conventional literature.